Theoretical Research of the Modification of Cycloidal Gear Used in High Precision RV Reducer - Ke Qingxun; Deng Xiaozhong; Su Jianxin; Nie Shaowu; Geng Longlong; Liang Shuaifeng (Jixie chuandong)
The second-order logarithmic superposition of modification quantity along the normal direction to the theory of conjugate tooth profile of cycloid gear of RV reducer is carried out,the cycloid tooth profile equation after the modification is deduced. By controlling the base number of the tooth profile modification and the coefficient of the tooth profile modification,the modification quantity control of the tooth profile curve at different position can be achieved. The difference between the second-order logarithmic profile modification method and the traditional parabola method is that the cycloidal wheel mainly involved in the tooth profile of the meshing working section is more closely to the theoretical tooth profile. The contact ratio of second-order logarithmic tooth profile modification is bigger,the transmission error curve has better symmetry,and the cycloidal wheel drive is more stable. This modification method has the advantages,a new way of thinking for the modification design of high precision RV reducer cycloid gear is provided.